281 Predicting neurodegeneration after traumatic brain injury. Issue 10 (13th September 2018) - SN, Graham Neil; E, Jolly Amy; J, Bourke Niall; Gregory, Scott; H, Cole James; J, Sharp David
Abstract : Background: Dementia rates are elevated after traumatic brain injury (TBI) and a subgroup develops chronic traumatic encephalopathy. Post-traumatic neurodegeneration can be measured by brain atrophy rates derived from neuroimaging, but it is unclear how atrophy relates to the initial pattern of injury. Objectives: To investigate the relationship between baseline TBI patterns and subsequent neurodegeneration measured by progressive brain atrophy. Methods: 55 patients after moderate-severe TBI (mean 3 years post-injury) and 20 controls underwent longitudinal MRI. Brain atrophy was quantified using the Jacobian determinant defined from volumetric T1 scans approximately one year apart. Diffuse axonal injury was measured using diffusion tensor imaging and focal injuries defined from T1 and FLAIR. Neuropsychological assessment was performed. Results: Abnormal progressive brain atrophy was seen after TBI (~1.8%/year in white matter). This was accompanied by widespread reductions in fractional anisotropy, in keeping with the presence of diffuse axonal injury. There was a strong negative correlation between FA and brain atrophy, whereby areas of greater white matter damage showed greater atrophy over time. Conclusions: The results show a strong relationship between the location of diffuse axonal injury and subsequent neurodegeneration. This suggests that TBI triggers progressive neurodegeneration through the long-lasting effects of diffuse axonal injury.